Drivers for eco-innovation in firms: an exploratory study in Spain. (17th June 2019) - Portillo-Tarragona, Pilar; Scarpellini, Sabina; Marín-Vinuesa, Luz María
The authors study the determinants of the behaviour of protection of the innovations through green patents, as an approximation of eco-innovative profile in firms. To this end, a large sample of firms from three regions in Spain is analysed through a binomial logit model. The authors find that age, size and financial performance significantly affect the choice of having green patents as eco-innovative conduct in firms. They also find that the sector of activity and the legal structure of firms are related with the choice of having, or not having, green patents to protect the innovations. Implications are explored for policy makers promoting the green patents registration and for practitioners introducing environmental improvement in the innovation processes.